Development of certain novel N-(2-(2-(2-oxoindolin-3-ylidene)hydrazinecarbonyl)phenyl)-benzamides and 3-(2-oxoindolin-3-ylideneamino)-2-substituted quinazolin-4(3H)-ones as CFM-1 analogs: design, synthesis, QSAR analysis and anticancer activity. - Alafeefy, Ahmed M.; Ashour, Abdelkader Elbadawy Abbas; Prasad, Onkar; Sinha, Leena; Pathak, Shilendra; Alasmari, Fatimah A.; Rishi, Arun K.; Abdel-Aziz, Hatem A. (Elsevier, 2015)
The reaction of N-(2-(hydrazinecarbonyl)aryl)benzamides 2a, b with indoline-2,3-diones 4ae in acidified ethanolic solution furnished the corresponding N-(2-(2-(2-oxoindolin-3-ylidene)hydrazinecarbonyl)phenyl)benzamides 5aj, respectively. Furthermore, 3-(2-oxoindolin-3-ylideneamino)-2-substituted quinazolin-4(3H)-ones 6aj were prepared by the reaction of 3-amino-2-arylquinazolin-4(3H)-one 3a, b with 4ae. Six derivatives of the twenty newly synthesized compounds showed remarkable antitumor activity against most of the tested cell lines, Daoy, UW228-2, Huh-7, Hela and MDA-MB231. Although these six compounds were more potent than the standard drug (CFM-1), indeed compounds 5b, 5d and 6b were the best candidates with IC50 values in the range 1.866.87, 4.4210.89 and 1.468.60 μg/ml and percentage inhibition in the range 77.188.7, 59.4184.8 and 75.488.0%, respectively. QSAR analyses on the current series of derivatives also have been performed for all five cancer cell lines and thus 10 statistically significant models were developed and internally cross validated.